Perceptions of SPED teachers on using picture exchange communication system (PECS) for autistic children: A correlational study - Lin, Hao-Chiang (Jacky) (Animo Repository, 2003)
The study focuses on the perceptions of public and private school teachers on the use of the Picture Exchange Communication System (PECS) on children with autism. The descriptive-comparative method of research was used. There were 40 respondents from which twenty came from the private special schools and the other 20 from the public special schools. These schools are located in the Manila, Quezon City and Makati area. The study revealed that the private school teachers perceived the Picture Exchange Communication System as a good source of teaching strategies. Their public school counterparts, however, viewed PECS as a good teaching tool. Both groups of respondents agree that PECS is a tool that can be used to develop communication in children with autism. Picture Exchange Communication System (PECS) does not only develop communication, but also decreases the maladaptive ways of the children with autism. These maladaptive ways are perceived to be the result of the lack of communication channels by which the children could express their needs and wants. Furthermore, the study showed that private school teachers are not familiar with the PECS, whereas public school teachers are very familiar with it.